Violência laboral e suas inter-relações com o sofrimento mental de enfermeiros no Triângulo Mineiro-MG - Galvão, Fernanda (2023)
This is a qualitative, transversal, exploratory and descriptive, study in order to analyze the perception of nursing professionals about violence in the work environment at the University Hospital of Triângulo Mineiro and its interrelationships with mental suffering, seeking strategies to minimize it. Data collection was carried out through 10 (ten) semi-structured interviews and organized into a textual corpus for submission to analyzes in the IRAMUTEQ software, in the Similarity Analysis and Cloud of Words tools, as well as the reading and interpretation of data through of Bardin's Content Analysis. The results showed that the professionals experienced violence at work, resulting in psychological and psychiatric treatments for symptoms of anxiety, depression, Burnout syndrome and panic disorder. Thus, five categories emerged from the analysis: Work relationships; Workplace violence and its facets; Nurses' workload; Difficulties of sick leave and Suggestions for improving working conditions. In this sense, when understanding the perception of professionals who face violence at work, it is necessary to seek prevention and mental health promotion strategies that involve this category in the hospital, using the interviewees' own suggestions, in order to find possible solutions to violence. Labor